Myxoid Chondrosarcoma of Maxilla in a Pediatric Patient: A Rare Case Report - Pranali Nimonkar; Nitin Bhola; Anendd Jadhav; Anuj Jain; Rajiv Borle; Rajul Ranka; Minal Chaudhary (Case Reports in Oncological Medicine)
Myxoid variant of chondrosarcoma is an uncommon potentially lethal malignant tumor which is even rare in pediatric age group. In the present paper, we report one such case of intermediate grade myxoid chondrosarcoma of left side of maxilla in a 12-year-old girl. The present case had a firm, painless, and lobulated growth in premolar-molar region which was associated with bicortical expansion. Maxillofacial imaging showed ill-defined radiolucency with displaced maxillary molars. Osteolytic changes were evident with the alveolus and walls of maxillary sinus. Owing to the age of the patient, surgical excision was selected as the modality of management followed by postoperative radiotherapy. This report encompasses the entire gamut of clinicopathological, radiological, and treatment modalities employed for chondrosarcoma.